A Robotic System for Remote Teaching of Technical Drawing - Yutaka Hiroi; Akinori Ito (MDPI AG, 2023)
This paper describes a robotic system that supports the remote teaching of technical drawing. The aim of the system is to enable a remote class of paper-based technical drawing, where the students draw the drawing in a classroom, and the teacher gives instructions to the students from a remote place while confirming the paper drawing. The robotic system has a document camera for confirming the paper, a projector, a flat screen to project a cursor on the paper, and a video conference system for communication between the teacher and the students. We conducted two experiments. The first experiment verified the usefulness of a projected cursor. Eight participants evaluated the comprehensibility of the drawing check instruction with or without the projected cursor, and the results suggested that the use of the cursor made the instructions more comprehensible. The second experiment was conducted in a real drawing class. We asked the students in the class to answer a questionnaire to evaluate the robotic system. The result showed that the students had a good impression (useful, easy to use, and fun) of the system. The contribution of our work is twofold. First, it enables a teacher in a remote site to point to a part of the paper to enhance the interaction. Second, the developed system enabled both the students and the teacher to view the paper from their own viewpoints.